2013
DOI: 10.1039/c3cy00349c
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the role of surface nitrate species in the oxidation of propene on a Pt-based diesel oxidation catalyst

Abstract: Enhancing the low temperature activity of diesel oxidation catalysts is important for cold-start conditions and the possible importance of nitrate species in oxidation reactions has been proposed although definitive evidence has not been reported. To investigate the possible role of surface nitrates, their adsorption and reactivity on a Pt-based diesel oxidation catalyst have been investigated using the Short Time on Stream (STOS) transient kinetic technique. The results provide for the first time definitive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…νCH features at 2962 cm 1 increased over the temperature ramp, further substantiating the formation of surface formate species on the alumina [30,31]. Other peaks related to the formate species can be observed at 1332, 1370, 1395 and 1665 cm 1 [21,23,32,33]. There is also evidence of bands at lower temperatures, 21852190 cm 1 , corresponding to CO on alumina's Lewis acid sites, as well as Hbonded CO on hydroxyl sites on the alumina at 2160 cm 1 [34].…”
Section: Co Tpomentioning
confidence: 64%
See 1 more Smart Citation
“…νCH features at 2962 cm 1 increased over the temperature ramp, further substantiating the formation of surface formate species on the alumina [30,31]. Other peaks related to the formate species can be observed at 1332, 1370, 1395 and 1665 cm 1 [21,23,32,33]. There is also evidence of bands at lower temperatures, 21852190 cm 1 , corresponding to CO on alumina's Lewis acid sites, as well as Hbonded CO on hydroxyl sites on the alumina at 2160 cm 1 [34].…”
Section: Co Tpomentioning
confidence: 64%
“…The formation of formates on Pt/Al 2 O 3 during propylene oxidation has been reported in the literature, with bands associated with said formates at 1332, 1370, 1395 and 1665 cm 1 , all of which were observed during the propylene TPO, Figure 9 a). Peaks that have been associated with an acetate species at 1457 cm 1 , and carboxylate species at 1580, 1642 and 1672 cm 1 [21,23,32,33] are also evident. Again the feature at 2962 cm 1 was observed (Figure 9 b)), and this time was present over the entire temperature range.…”
Section: H 6 Tpomentioning
confidence: 93%
“…For each test, the catalysts were evaluated at different temperature varied from 250 to 500 °C. In situ diffuse reflectance infrared Fourier-transform J o u r n a l P r e -p r o o f spectroscopy-mass spectrometry (DRIFTS-MS) characterisation of the catalysis over the developed catalysts was performed with the detailed procedure described elsewhere [1,23]. Specifically, for each experiment, the catalyst was loaded into a ceramic crucible in the IR cell and reduced (at 400 C in a 10% H2/Ar flow for 1 h then cooled to 40 °C).…”
Section: Catalytic Co2 Hydrogenation Under Thermal and Ntp Conditionsmentioning
confidence: 99%
“…Wilbum et al found that a smaller Pt–Pd particle size could promote the formation of aluminum sulfate species in investigating SO 2 adsorption and desorption by TPD and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). Meanwhile, IR studies could efficiently help to investigate the intermediate species. Recently, Liu et al adopted in situ DRIFTS and found the specific changes of NO x related species in bismuth compounds. In the deNO x process, it was observed that SCR performance were improved by active NO x species. , Furthermore, how adsorption active sites and acid sites affect the adsorbed NO x species in NH 3 –SCR reaction has been investigated by Zhang group. , Thus, it was interesting to study the effect of noble bimetal particle size on the catalytic NO oxidation activity of the monolithic aged DOC catalysts by in situ FTIR.…”
Section: Introductionmentioning
confidence: 99%